TOPOGRAPHIC MAPPING SUPPORT IN THE SOUTH AFRICAN MILITARY DURING THE 20TH CENTURY - Jacobs, André; Smit, Hennie (Scientia Militaria - South African Journal of Military Studies, 2012)
Maps provide a base for all intelligence operations and strategic and tactical decisions, supporting the planning and execution of all battlefield functions. The development of military mapping support in South Africa, related closely to the development of aerial photography, may be divided into five, sometimes overlapping, phases. The first of these phases spans the years from 1840 to 1930 and is characterised by the gradual recognition that aerial photographs could be used for mapping. Two major conflicts – the Anglo Boer War and the First World War – marked this development. The Second World War is the key event of the second phase (1930–1950), which witnessed a rapid expansion of aerial photo coverage. The third phase (1945–1960) saw the overemphasising of interpretation techniques rather than the analytical use of results, which was rectified during the fourth phase (1955–1962) when the focus shifted to the applied uses of air-photo interpretation. During the third and fourth phases the topographic mapping support ability of the South African military was expanded. The fifth phase (since 1960) commenced with the expansion of data gathering and analysis into portions of the electromagnetic spectrum beyond the small visible sector. During this period the protracted nature of the conflict on the northern border of Namibia (formerly South West Africa) and the war in Angola focused attention on the South African military mapping system. The National Service system allowed for the expansion of mapping units and the thorough mapping of large areas adjoining our borders. Through all five phases, mapping in the South African military has advanced from hand-produced maps to the utilisation of complex equipment that satisfies the sophisticated mapping needs of a modern defence force. This paper presents a brief history of both mapping support and the mapping units that have served within the South African theatre during the twentieth century. In doing so, the operational importance of topographic maps is also highlighted.